Maternal vitamin D deficiency and fetal distress/birth asphyxia: a population-based nested case–control study. Issue 9 (22nd September 2016) - Lindqvist, Pelle G; Silva, Aldo T; Gustafsson, Sven A; Gidlöf, Sebastian
Abstract : Objective: Vitamin D deficiency causes not only skeletal problems but also muscle weakness, including heart muscle. If the fetal heart is also affected, it might be more susceptible to fetal distress and birth asphyxia. In this pilot study, we hypothesised that low maternal vitamin D levels are over-represented in pregnancies with fetal distress/birth asphyxia. Design and setting: A population-based nested case–control study. Patients: Banked sera of 2496 women from the 12th week of pregnancy. Outcome measures: Vitamin D levels were analysed using a direct competitive chemiluminescence immunoassay. Vitamin D levels in early gestation in women delivered by emergency caesarean section due to suspected fetal distress were compared to those in controls. Birth asphyxia was defined as Apgar <7 at 5 min and/or umbilical cord pH≤7.15. Results: Vitamin D levels were significantly lower in mothers delivered by emergency caesarean section due to suspected fetal distress (n=53, 43.6±18 nmol/L) compared to controls (n=120, 48.6±19 nmol/L, p=0.04). Birth asphyxia was more common in women with vitamin D deficiency (n=95) in early pregnancy (OR 2.4, 95% CI 1.1 to 5.7). Conclusions: Low vitamin D levels in early pregnancy may be associated with emergency caesarean section due to suspected fetal distress and birth asphyxia. If our findings are supported by further studies, preferably on severe birth asphyxia, vitamin D supplementation/sun exposure in pregnancy may lower the risk of subsequent birth asphyxia.